Vestibuloplasty following denture hyperplasia resection with diode laser - Kannyadath Padmanabhan Akhil; Rashmi Paramashiviah; Munivenkatappa Lakshmaiah Venkatesh Prabhuji (Wolters Kluwer Medknow Publications, 2020)
Denture hyperplasia is a common clinical finding in patients wearing dentures. In this case report, a patient who was treated for denture hyperplasia presented with a post operative complication which led to inadequate vestibular depth. Inadequate vestibule is a common challenge dental surgeons encounter while considering fixed or removable prosthesis and implants. Objective is to achieve acceptable retention and aesthetics for the prosthesis by increasing the vestibular depth and also to manage the complication encountered during the resection procedure. Several techniques have been employed to increase the vestibular depth and the width of attached gingiva in the literature. In this case the denture hypereplasia was resected using diode laser which resulted in bone necrosis and opening of the wound post surgically. This was managed with curettage and PRF application. Following this the patient presented with inadequate vestibular depth. Vestibuloplasty was performed with Diode laser to deepen the vestibular depth and augment keratinized tissue to facilitate prosthetic rehabilitation. Three months following vestibuloplasy, patient presented with adequate vestibule. At six months follow up there was sufficient keratinized tissue to facilitate prosthetic rehabilitation. This case presents a unique way of managing a complication encountered after denture hyperplasia resection followed by vestibuloplasty with diode laser. The results obtained were clinically acceptable. PRF provides excellent results when used for the management of surgical complications like wound exposure. Laser technique is optimal for the treatment of soft tissue defects and is proven to be ideal for vestibuloplasty.